Efeitos dos leilões de energia no desenvolvimento da cadeia de produção da fonte eólica - Oliveira, Francis Dall'Orto de (2017)
This paper investigates the wind power commercialization effects in energy auctions in Brazil on its supply chain in the light of a triangular (qualitative and quantitative) approach that includes the following steps: first, the contracting environments of electric energy and energy market were studied in order to find quantitative variables with influence on a commercialization of wind power in auctions; afterwards, multivariate and simple regressions were carried out to conclude whether as variables found have influence on an amount of wind energy contracting in the auctions and on the wind farms building, respectively; after that, was made an analysis on the elements that compose the wind farms; In addition, 21 experts from following areas were interviewed: energy commercialization market, government agencies, wind power generation companies, concessionaires and university professors representing eight Brazilian states. Upon the interviews a treatment denominated Content Analysis was made, in order to categorize the opinions and obtain relevant information. Finally, these information were gathered and analyzed together to provide the results, and suggestions were made for future researches. Although the universe of auctions in Brazil is still small, which makes impossible the realization of robust statistical inferences, the results obtained suggest that the commercialization of wind power through auctions has a direct influence on the development of the supply chain of this source. However, gaps need to be filled in to make auctions more reliable and attractive to investors.